Anu Põder - space for my body - Põder, Anu 1947-2013; Alemani, Cecilia 1977-; Sosnowska, Agnieszka 1971- (Skira, 2023)
Anu Põder (1947-2013) is one of Estonia’s most revelatory voices of the last five decades. Her work has stood out since the 1970s as uniquely crafted, originally conceived, and deeply personal. Yet, because it was somehow out of sync with the then established art landscape in Estonia, it has been overlooked for many years. Põder is known for exploring the human body, highlighting the fragility, impermanence, and ephemerality of life in a series of highly evocative sculptures. Throughout her career, she employed unconventional materials such as textile,?wax, plaster, soap, plastic, and wood to compose delicate assemblages. Working at the cusp of two major eras –– the Soviet occupation of Estonia, which began in 1940, and the new independence gained in 1991 –– Põder embraced the uncertainty of identity of the Estonian people, working as one of the very few women artists in a decidedly male context and focusing on female subjectivity alongside other international artists such as Magdalena Abakanowicz, Louise Bourgeois, Ana Mendieta, and Alina Szapocznikow. This illustrated monograph presents the latest research on Anu Põder work, featuring contributions by renowned authors and curators: Dina Akhmadeeva, Cecilia Alemani (co-editor), Ann Coxon, Agata Jakubowska, Linda Kaljundi, Marika Kuzmicz, Adomas Narkevicius, Bojana Peijc, Agnieszka Sosnowska (co-editor) and Triin Tulgiste-Toss. Anu Põder: Space for My Body offers a comprehensive survey of her artistic journey, highlighting her remarkable contribution to European art. The monograph is yet another chapter in the ongoing series initiated by Muzeum Susch dedicated to the rediscovery of women artists who have been neglected by the main discourses and canons of art history
Impressum: "This book was published on the occasion of the exhibition "Anu Põder: Space for My Body", Muzeum Susch, 3 January - 30 June 2024"
Keywords: Põder, Anu -- 1947-2013; Ausstellungskatalog -- Muzeum Susch -- 03.01.2024-30.06.2024 -- Susch